Evaluation of ultrasound‐assisted microwave hot air convective drying Chinese hickory—Drying kinetics and product's quality properties. (6th September 2021) - Zhang, Jigang; Li, Maoye; Ding, Zhien; Wang, Chuyan; Cheng, Jianghua
Abstract: The fresh Chinese hickory nuts ( Carya cathayensis sarg.) were exposed to airborne ultrasound‐assisted convective drying and microwave‐assisted convective drying, as well as their combination. We investigated the effect of different drying schemes on process kinetics and quality characteristics. The global model of drying kinetics based on coupled ordinary differential equations was used to describe the moisture and material temperature profiles during drying. Application of ultrasound and microwave in convective drying reduced drying time in the range of 14.0–56.6%, but the maximum savings was found for simultaneous exposure of convection, ultrasound, and microwave with the range of 73.6–84.2%. The globally mathematical model was successfully used to simulate the real drying kinetics processes. The quality properties about the content of heat‐sensitive bioactive substances such as phenolic, flavonoid, proanthocyanidin, individual phenolic compounds, as well as antioxidant capacity in convective drying assisted with microwave (100 W) and ultrasound (200 W; CU2M1) are found to be significantly higher than the other groups. The results allow stating ultrasound increase drying efficiency, as expected by reducing the drying time there is less damage to the product. Practical Application: In this work, we designed an experimental scale hybrid dryer that equipped with hot‐air convective drying, ultrasound generator and microwave drying system to dehydrate Chinese hickory nut and the effect of different drying schemes on the drying kinetics and product characteristics were investigated. This is an innovative technology of microwave and ultrasound hybrid drying to produce dried hickory products. Application of ultrasound and microwave in convective drying reduced drying time in the range of 14–56.6%, but the shortest drying time was observed for simultaneous action of convection, ultrasound, and microwave. The results of qualitative analysis showed a product improvement due to ultrasound as compared to convective drying and microwave‐convective drying. Abstract :